Metodologi Dan Pengaruh Ideologis Dalam Tafsir Nusantara - Ningrum, Dzuriya M.L (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2018)
This article tries to discuss one of the interpretations of Indonesian scholars, Kyai Asmuni Al Jaruny, namely the interpretation of Muawidzatain. It is interesting to discuss because this interpretation is the work of Indonesian Ulama who use Arabic and are written by pesantren people. This study seeks to reveal how the methodology and influence of the author's ideology in the interpretation. In interpreting Kyai Yasin Asmuni, many are inclined towards kebathinan which in the world of interpretation is known as the epistemology of irfani or shufi. The tendency of the Sunni school is also felt in its interpretation. While methodologically this interpretation is included in the category of interpretation of mawdhu'i fi suwar with the form of presentation of bi al-Ma'thur and ra'yi at the same time. This was evident, when Kyai Yasin Asmuni interpreted the verses of the Koran with his ijtihad, starting from aspects of the Arabic language as well as discussing the existing Sufi aspects and several other aspects. But on the other hand he still uses history as the basis of his interpretation. This research is a library research qualitative research and romantic hermeneutics as the approach.